Retrospective analysis of the epizootic situation of enzootic bovine leukosis in Ukraine in 1994–2019 - L. Y. Korniienko; A. V. Pyskun; T. M. Tsarenko; V. V. Ukhovskyi; G. V. Kyivska; O. A. Moroz; V. L. Kovalenko; G. B. Aliekseieva (Regulatory Mechanisms in Biosystems, 2020)
In Ukraine, prevention and control measures of bovine leukosis were regulated by relevant legislation, regulations and instructions developed in the period 1960–1992. Currently, the instruction on prevention and rehabilitation of this disease in cattle is used (approved in 2007). According to it, the identification of infected animals is carried out from 6 months of age by serological (first scheme in AGID or another in ELISA) and genomic (PCR) methods. The infected animals are removed from the herd or slaughtered. In general, because of the diagnostic and preventive measures carried out during the analyzed period (26 years) 10 519 farms were rehabilitated from leukosis (2 346 affected farms remained from previous years). At the same time, more 4 million infected cattle were slaughtered. The majority of affected farms (more than 1 000) were registered in the period between 1994 (2 346 farms) and 2003 (1 247 farms). Since 2014, the number of affected farms has remained mostly below 10 and the number of infected cattle has decreased to 2 000 animals per year. At the same time, the number of rehabilitated farms also decreased (from 1 307 farms in 1998 to 4 farms in 2014). The same trend was registered with the dynamics of the number of animals that were removed from the herd due to leukosis. Thus, in 1995 and 1997 their numbers were 321 178 and 558 649 animals, respectively, and in 2014 it was 1 124. The obtained indicators of intensity and extensiveness of the epizootic process show that the incidence rate was maximal during 1998–2000 and amounted to 3.7–4.3%. The maximum indicators of the coefficient of affection were recorded in 1997–2000 and equal 11.8–15.3%. The rate of foci remained on the level of 90–270 throughout the all analyzed period. During 2008–2019, specialists of the Ukrainian veterinary laboratories investigated more than 47 million samples of cattle blood sera for enzootic bovine leukosis by AGID and ELISA. However, despite the significant diagnostic work, the important factor in the decrease of the number of affected farms and infected animals is the decrease in the total number of cattle in Ukraine (almost 22 million animals in 1994 against 3 million in 2019). Graphic trends of these indicators are comparable and agree with the decrease in the number of cattle in our country by analyzed period. After 2014, the number of affected farms ranged 10–17 per year (mostly in private households). However, the full recovery of cattle in Ukraine from bovine leukosis has not taken place, although our country is closer than ever to this.